Implementation of Continous Band Sealer to Improve Packaging Quality of MSMEs Dapur Sangit Wandanpuro Village Bululawang - Herwanto, Heru Wahyu; Muhammad Afnan Habibi; Sujito, Sujito; Arya Kusumawardana; Dimas Jundan A; Shandy Krisnawan (Khidmatuna (Jurnal Pengabdian Kepada Masyarakat), 2023)
The post-pandemic era is a post-pandemic era where all MSME players are maintaining their businesses and must even be able to increase their businesses. The obstacles experienced by MSMEs Dapur Sangit, Wandanpuro Village, Bululawang, Malang Regency, which are engaged in catering and produce shredded milkfish processed foods, occur in the process of packing or packaging products that are inefficient and untidy. In addition, the product packaging process is still applying conventional technology by using a hand sealer manually. The impact of the packaging process with this conventional tool certainly makes the packaging untidy and there are defects in the packaging so that it will affect product quality and have an impact on reducing quality and selling value in the market. The purpose of this community service program is to apply Appropriate Technology (TTG) in the form of an automatic Continuous Band Sealer machine that functions to improve packaging quality, reduce costs if still applying conventional technology and increase product durability. The results of the service carried out went smoothly and could improve the quality of product packaging for MSMEs Dapur Sangit.